Design and development of a micro-EDM using micro-actuator tool feed control system - Mohd Hishammudin, Donnie (2010)
This thesis deals with the development of the Micro-EDM with Micro-Actuator Tool Feed Control System. The objective of this thesis is to fabricate the machine by implementing the sensor by using the Amplified Piezoelectric Actuator as tool feed control system. The thesis describes the components that are essential to fabricate the machine. This research is done because there is a huge demand in the production of microstructures by a non-traditional method which is known as Micro-EDM. Micro- EDM process is based on the thermoelectric energy between the workpiece and the electrode. This research also conducts a study about the dielectric flushing that is one of the most important parameters in Micro-EDM. The dielectric flushing removes the unwanted waste metal particles that will disrupt the machining process and will eventually affect the machining accuracy and precision. The development of the control circuit is also discussed in this thesis whereas the circuit is analyzed in OrCAD software to confirm the circuit validity for the use of controlling the Micro-EDM. Micro-EDM is a newly developed method to produce micro-parts which is in the range of 50μm - 100μm. Micro-EDM is an efficient machining process for the fabrication of micro-metal hole with various advantages resulting from its characteristics of non-contact and thermal process. A pulse discharges occur in a small gap between the process of melting and vaporization. In this thesis describes the characteristics, the material removal rate, and the dielectric circulation system that are essential in the Micro-EDM process.